Gender transformative approaches in agriculture - Vos, Andrea (CGIAR Collaborative Platform on Gender Research, 2018)
Presented by Andrea Vos (CGIAR Collaborative Platform for Gender Research/KIT), as part of the Annual Gender Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 27-28 September 2018.